Teachers' Professional Competence in Teaching - Philips Ratu Bunga; Merri Natalia Situmorang; Endang Pasaribu (Journal of World Science, 2025)
Aging is a natural and inevitable part of life that everyone will experience. Preparing for old age is essential to maintain a spirited and meaningful life despite the challenges, such as family struggles or illness, that many elderly individuals face. In Christianity, old age is regarded as a blessing from God—a time to find joy in His steadfast love and peace. This perspective encourages the elderly not to fear their physical limitations, trusting in God's ongoing care and protection. This study explores how the elderly can continue to work, serve God, and love others with unwavering faith until they are called to the Kingdom of Heaven. Employing a qualitative research method grounded in theories about aging and supported by observational data, the study reveals that the church plays a crucial role in empowering the elderly through active participation in church services. The findings emphasize the importance of fostering spiritual engagement and community involvement among older people to enhance their well-being and sense of purpose. This research contributes valuable insights for religious communities seeking to support aging members, highlighting the need for inclusive practices that honor and utilize the gifts of older adults.